2006
DOI: 10.4103/0019-5278.27303
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the respiratory impairments among the male beedi workers in unorganized sectors

Abstract: Aims: The dust of tobacco enters the respiratory system of beedi workers through inhalation during beedi-making and causes respiratory impairments. The aim of the present study is to evaluate the pulmonary functional status of male beedi workers and to detect the pulmonary function impairments among these workers. Materials and Methods: A standard questionnaire was followed to note the symptoms like cough, breathlessness, morning cough and chest tightness. The tendu leaves contain fungal spores in different ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Study conducted by B.P Chattopadhyay et al 8 have reported similar observations. X -ray chest confirmed lung parenchymal changes have also been reported among workers exposed to tobacco dust for more than 30years 12 .…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Study conducted by B.P Chattopadhyay et al 8 have reported similar observations. X -ray chest confirmed lung parenchymal changes have also been reported among workers exposed to tobacco dust for more than 30years 12 .…”
Section: Discussionsupporting
confidence: 62%
“…Tobacco dust contains various immunologically active and toxic substances. It has been established that occupational chronic exposure to the dust of tobacco leaves is associated with significant increase in the occurrence of respiratory disorders 8,10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobacco dust generated during beedi making was reported to act as an initiator or promoter of skin tumors in S/RV Cri-ba mice (Bagwe et al, 2004). A low prevalence of chronic respiratory symptoms was found in control workers and the prevalence of cough with breathlessness, morning cough were higher among workers exposed to tobacco dust than the control (Chattopadhyay and Kundu, 2006).…”
Section: Discussionmentioning
confidence: 95%